2022
DOI: 10.1038/s42003-022-03422-9
|View full text |Cite
|
Sign up to set email alerts
|

A precision medicine approach to metabolic therapy for breast cancer in mice

Abstract: Increasing evidence highlights approaches targeting metabolism as potential adjuvants to cancer therapy. Sodium-glucose transport protein 2 (SGLT2) inhibitors are the newest class of antihyperglycemic drugs. To our knowledge, SGLT2 inhibitors have not been applied in the neoadjuvant setting as a precision medicine approach for this devastating disease. Here, we treat lean breast tumor-bearing mice with the SGLT2 inhibitor dapagliflozin as monotherapy and in combination with paclitaxel chemotherapy. We show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Dapagliflozin is also an effective agent in ameliorating hyperinsulinemia, which causes BC progression in DM patients [ 39 ]. However, the inhibitors’ effect is limited to BC with a specific mutation, namely Pten-driven EMT6 tumors and HRAS-driven Ac711 tumors [ 40 ]. Several clinical trials are ongoing to determine the safety and efficacy of SGLT2 inhibitors when used in combination with other BC chemotherapy ( Table 1 ).…”
Section: Mrs Targeting Glucose Metabolismmentioning
confidence: 99%
“…Dapagliflozin is also an effective agent in ameliorating hyperinsulinemia, which causes BC progression in DM patients [ 39 ]. However, the inhibitors’ effect is limited to BC with a specific mutation, namely Pten-driven EMT6 tumors and HRAS-driven Ac711 tumors [ 40 ]. Several clinical trials are ongoing to determine the safety and efficacy of SGLT2 inhibitors when used in combination with other BC chemotherapy ( Table 1 ).…”
Section: Mrs Targeting Glucose Metabolismmentioning
confidence: 99%
“…Dapagliflozin blocks glucose uptake in the renal tubules, allowing it to be excreted in the urine. She showed that in a mouse model of triple‐negative breast cancer, dapagliflozin enhanced the efficacy of chemotherapy specifically in tumors driven by mutations upstream of insulin signaling 92 . Perry's group is designing a clinical trial in obese women with TNBC to see if similar effects are seen in humans.…”
Section: Frontiers In Immunometabolismmentioning
confidence: 99%
“…The utilization of antidiabetic treatment presents a potentially valuable approach for the treatment of melanoma, as well as various other types of cancers. [36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Antiadipogenic Drugs For Melanomamentioning
confidence: 99%
“…The use of antiadipogenic drugs such as metformin and thiazolidinediones (TZD)—peroxisome proliferator–activated receptor γ (PPARγ) agonists—has shown promise in slowing down the spread of a degree of cancers such as melanoma. The utilization of antidiabetic treatment presents a potentially valuable approach for the treatment of melanoma, as well as various other types of cancers 36–47 …”
Section: Antiadipogenic Drugs For Melanomamentioning
confidence: 99%